(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article analyzes modern trends in the development of fine arts and design methodology, innovative technologies, creative approaches, and integration into the education system. Also, based on national and world experience, new stages of art education, methodological approaches, and their significance in the process of aesthetic education are highlighted.